2019
DOI: 10.1111/add.14518
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of smoking cessation interventions in low‐ and middle‐income countries: a systematic review and meta‐analysis

Abstract: Aims To summarize evidence for the efficacy of smoking cessation interventions in low‐ and middle‐income countries (LMICs). Design Systematic review and meta‐analysis of randomized controlled trials. Setting LMICs as defined by the World Bank. Participants Adult current cigarette smokers residing in LMICs. Interventions Behavioral and/or pharmacotherapy smoking cessation interventions. Measurements PubMed MEDLINE, EMBASE (embase.com), Cochrane Central Register of Controlled Trials (Wiley), PsycINFO (Ebsco), Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…While TMR seems to be more cost-effective than OSR because of the low-intensity design, the intervention costs of the two groups were similar. The average costs per participant for recruitment and intervention delivery were low (US$21.6), suggesting a high applicability of our brief intervention models in places with limited health-care resources [30]. Caution is needed in interpreting the results from the post-hoc 18-month follow-up, as only half the participants were successfully interviewed.…”
Section: Discussionmentioning
confidence: 99%
“…While TMR seems to be more cost-effective than OSR because of the low-intensity design, the intervention costs of the two groups were similar. The average costs per participant for recruitment and intervention delivery were low (US$21.6), suggesting a high applicability of our brief intervention models in places with limited health-care resources [30]. Caution is needed in interpreting the results from the post-hoc 18-month follow-up, as only half the participants were successfully interviewed.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO estimated that there are 2 billion alcohol users, 1.3 billion tobacco users, and 185 million illicitdrug users worldwide [2]. Currently, 80% of tobacco users live in low-and middle-income countries (LMICs) [3] and also, 80% of tobaccorelated deaths are predicted to occur in LMIC by 2030 [4]. Smoking and alcohol abuse attributable to 20% of tuberculosis (TB) disease worldwide and collectively made India a home of world's 27% of TB patients in 2017 [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable to know that smokers did not use this service because they were not aware of the service or they did not consider it helpful. A recent systematic review of randomised controlled trials showed that nicotine replacement therapy, behavioural counselling and brief advice are effective interventions in LMICs [ 30 ]. Nevertheless, implementing these interventions in healthcare settings remains a big challenge in many LMICs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%